2020
DOI: 10.1001/jama.2020.8133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Dexamethasone on Major Complications and Mortality Among Infants Undergoing Cardiac Surgery

Abstract: IMPORTANCECorticosteroids are widely used in pediatric cardiac surgery to blunt systemic inflammatory response and to reduce complications; nevertheless, their clinical efficacy is uncertain.OBJECTIVE To determine whether intraoperative administration of dexamethasone is more effective than placebo for reducing major complications and mortality during pediatric cardiac surgery. DESIGN, SETTING, AND PARTICIPANTSThe Intraoperative Dexamethasone in Pediatric Cardiac Surgery was an investigator-initiated, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 35 publications
2
34
0
1
Order By: Relevance
“…We did not find an association between a history of diabetes and the effect of dexamethasone on the primary outcome. In accordance with our data, it has been shown recently that high doses of dexamethasone administered perioperatively to children after cardiac surgery was not associated with major harm 40…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We did not find an association between a history of diabetes and the effect of dexamethasone on the primary outcome. In accordance with our data, it has been shown recently that high doses of dexamethasone administered perioperatively to children after cardiac surgery was not associated with major harm 40…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our data, it has been shown recently that high doses of dexamethasone administered perioperatively to children after cardiac surgery was not associated with major harm. 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Systemic steroid use has failed to reduce the length of mechanical ventilation after cardiac surgery in pediatric studies, including the present study. 7,8,25,26 Even though in an RCT on adult patients, high-dose dexamethasone helped shorten mechanical ventilation after cardiac surgery, the pediatric study cohorts may have been too small to answer this question. 27 Furthermore, in the present study, because postoperative lung edema was only mild and lung injury scarce, the SDC regimen may have lacked significant effect on major clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of randomized controlled trials showed that the prophylactic use of corticosteroids in patients with heart operation under CPB did not bring any benefits, but increased the risk of myocardial infarction, prolonged the time of mechanical ventilation. [ 10 , 13 , 14 , 18 ] Adult cardiac surgery guidelines and clinical routine cardiac surgery in adults and children are not used in preventive corticosteroids. However, the clinical effects of corticosteroids are dose-dependent.…”
Section: Discussionmentioning
confidence: 99%